Descriptions of three new species of the genus Cheilosia Meigen from China (Diptera, Syrphidae) - Barkalov, Anatolij V.; Ståhls, Gunilla (Zootaxa, 2015)
Three species of genus Cheilosia (Diptera, Syrphidae: Eristalinae) from China are described as new to science, Cheilosia bullabucca Barkalov & Ståhls sp. n., C. lamproptera Barkalov & Ståhls sp. n. and C. yunnanensis Barkalov & Ståhls sp. n. We provide species descriptions and keys for their identification. The phylogenetic placements of the taxa was estimated based on their morphological characteristics and by analysing the taxa under parsimony using a mtDNA COI sequence dataset including a comprehensive set of Palaearctic previously generated Cheilosia spp. sequences representing all major subgenera. Based on both their morphological affinities and the molecular data. The Chinese taxa were placed in the subgenera Eucartosyrphus (C. bullabucca), Cheilosia s. str. (C. oblonga), Floccocheila (C. versicolor) while C. yunnanensis was not resolved as member of Cheilosia s. str. based on DNA despite sharing morphological characteristics with the subgenus. As the name Cheilosia (Nephocheila) prima Barkalov & Cheng from China is a junior homonym of Cheilosia (Cartosyrphus) prima Hunter, 1896 from the Nearctic region, for the Chinese species the new name Cheilosia (Nephocheila) primaria Barkalov & Ståhls nomen nov. is proposed.